The importance of effective corporate governance / Prof. Madya Shafi Mohamad (Universiti Teknologi MARA, Sarawak, 2005)
The term corporate governance came into vogue following the Asian Economic Crisis in July 1997 and has since been bandied about quite frequently in the business press. This paper looks at some of the different definitions of corporate governance as well as the importance of corporate governance. It then looks at the core components that contribute to effective governance by looking at the model developed by the Organization for Economic Cooperation and Development (OECD) Business Sector Advisory Group on Corporate Governance, or more commonly known as the Millstein Report. It then goes on to discuss the importance of efforts to raise the awareness of corporate governance globally keeping in mind the differences in national cultures as well as differing social and economic priorities between sovereign nations. It then concludes by saying that at this point in time, a consensus on a single model of corporate governance is both unlikely and unnecessary since over time the exigencies of the capital market (market forces) will lead to increasing convergence in practice between countries.